Construção de um diagnóstico de enfermagem na categoria promoção da saúde para o crescimento/desenvolvimento : estudo em lactentes - Monteiro, Flávia Paula Magalhães (2013)
The study aimed to construct a nursing diagnosis child growth and development in the health promotion category. Study methodology, developed in three stages of validation of nursing diagnoses, as recommended by Hoskins (1989): The concept analysis, expert validation and clinical validation. To concept analysis was used as the reference model concept analysis proposed by Rodgers (2000) and integrative literature proposed by Mendes, Silveira and Galvão (2008). For selection of productions, were searched five databases: Scopus, Pubmed, Cinahl, Lilacs and Cochrane with descriptors: growth and development, infant, preschool and their synonyms in English and Spanish. The concept analysis was supported by 83 studies. Regarding the concepts of growth and development phenomena, there is still much controversy regarding the use of them in order that literature brings phenomena dissociated or aggregated. The growth covers physiological aspects related to changes in size and shape, referring to body measurements. Development is defined as a broad and complex phenomenon, integrating areas: mental, cognitive, behavioral, perceptual, motor, physical. The literature has contributed to the development of fifteen defining characteristics in distributed domains: six in the physical, cognitive and six in three in psychosocial. The validation step with experts understood the appreciation of the instrument consists of two parts: 1st) characterization of specialists and 2nd) diagnostic proposal: title, setting, area 13, defining characteristics with their conceptual definitions and operational (empirical references) by 22 experts in area of child health, predominantly female (94.4%), doctors (55.6%), concentrated in the Northeast (61.1%), which exercised its activities in the past year as teachers in educational institutions (HEI) (83.3%). The time specialist training was on average 13.1 years (± 8.5). As for the structure of diagnosis, most of them pointed out that the title referred to improved child development (61.1%) as most appropriate for the nursing diagnosis under construction. All experts agreed that the diagnosis should be included in the proposed area 13 growth / development (100%), and class that distributes phenomena: 1 - and 2 growth - development (55.6%). Most experts chose the concept 1 (55.6%). Part of experts suggested adding the instrument of some peculiarities of the infant phase regarding defining characteristics. The clinical validation was performed with 45 infants assessed during the consultation childcare in a Family Health Center. The majority were male (55.6%). Half of the infants showed age of 5 months, with mothers / guardians with an average age of 24 years. The defining characteristics obtained high sensitivity (above 90%), positive predictive values above 65%, negative predictive values above 66%, however, low levels of specificity (less than 32%). Therefore, they are good indicators predictive of the occurrence of the proposed nursing diagnosis. Thus, six defining characteristics, as noted in the study, are suitable for composing the nursing diagnosis Provision for growth and development of infants improved.